THE RELATIONSHIP BETWEEN SELF-REGULATED LEARNING AND PARENT’S ATTENTION WITH MATHEMATICS LEARNING OUTCOMES IN STUDENTS CLASS XI - Herlina Janie Setiawan; Widayati Widayati (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Many factors determine student learning outcomes. Self-regulated learning and parent’s attention are some of the factors suspected that relate to student learning outcomes. This study aims to determine the presence or absence of a positive relationship between and significant relationship among the self-regulated learning and parent’s attention with learning achievement mathematics students class Vocational High School (SMK) 1 Bantul in the first semester of the academic year 2018/2019. The populations of this study were all students of class XI consisting of 6 classes with 188 students. Samples were taken using a random sampling technique. The data collection techniques used the non-test technique by a questionnaire and test. The test research instruments were: validity tests, different power tests, reliability tests, and independence tests. The writer uses product-moment correlation analysis and multiple linear regression analysis to analyze the data. The results of the study showed that there was a positive and significant correlation between: self-regulated learning and parent’s attention to the mathematics learning outcomes with R2 = 0.6869, coefficient determine 0,4718 and Fcount = 12.0598  Ftable = 3.3541, with RC = , RC  =  and EC = , EC  = .